Corn silage supplementation for sheep eating annual ryegrass - Bibiana Lima Fonseca; João Gabriel Rossini Almeida; Ederson Américo de Andrade; Gutierri Tales Raupp; Henrique Mendonça Nunes Ribeiro-Filho (Semina: Ciências Agrárias, 2018)
Food intake is determinant in the production process and can be modified when more than one type of forage is supplied in the diet. The aim of this study was to evaluate the effects of supplementation with corn silage + soybean meal (9:1 based on DM) in the proportion of 10 g DM kg?1 live weight (LW) for lambs receiving pre-dried ryegrass (Lolium multiflorum Lam) in two forage supply levels: ad libitum or restricted (60% of the consumption ad libitum). Eight castrated male sheep crosses Texel × Criollo (average of 31.5 ± 2.2 kg LW) were used in an experimental design of 4 × 4 Latin square. Each experimental period was performed for 19 days, with 14 days for adaptation and 5 days for collections. Animals were fed three times a day (08h00, 11h30, and 16h30). Supplemented animals received corn silage at 08h00 and ryegrass silage at 11h30 and 16h30. The substitution rates (kg DM consumed forage per kg DM consumed silage) were 0.93 for animals with a supply of ryegrass ad libitum and zero for those receiving the same in a restricted amount. The digestible OM (DOM) intake and nitrogen retention did not vary with supplementation in animals that received ryegrass ad libitum but increased in those with restricted supply. However, animals with restricted supply and supplemented had a less digestible OM intake and nitrogen retention than the average of those that received ryegrass ad libitum. Organic matter digestibility and efficiency of microbial protein synthesis were not affected by treatments, but the digestibility of NDF and ADF was lower in supplemented animals when compared to those non-supplemented and in restricted supply when compared to consumption ad libitum. Even with supplementation, feed restriction of base forage can limit the daily intake of digestible OM and the daily retention of N in sheep.